Perception On The Effectiveness Of Internal Auditors In Southwest Aceh Regional Government - Darliefa, Darliefa (2013)
In the globalization era, it is important to ensure that the objective of the organization is achieved effectively, efficiently and economically. Increase demand from society are accountability, transparency and regulatory pressure in government sector push Internal Auditors to seek ways to enhance effectiveness in their work. This study estimates the score of effectiveness level of Internal Auditors as perceived by Internal Auditors themselves and the Head of Agency. In addition, the study also examines factors influencing the score of effectiveness of Internal Auditors as perceived by Internal Auditors themselves and the Head of Agency.